Four paths to Jerusalem : Jewish, Christian, Muslim, and secular pilgrimages, 1000 BCE to 2001 CE - Janin, Hunt, 1940- (McFarland & Co., 2006)
Jerusalem has long been one of the most sought-after destinations for the followers of three world faiths and for secularists alike. For Jews, it has the Western (Wailing) Wall; for Christians, it is where Christ suffered and triumphed; for Muslims, it offers the Dome of the Rock; and for secularists, it is an archeological challenge and a place of tragedy and beauty. This work concentrates on Jewish, Christian, Muslim, and secular pilgrimages to Jerusalem over the last three millennia, drawing from over 165 accounts of travels to the ancient city. Chapters are devoted to ghostly and other pilgrims, the significance of Jerusalem, the beginnings of the pilgrimage in the time of kings David and Solomon, pilgrimages under Roman and Byzantine rule, Christian and Muslim pilgrimages in the early Islamic period, pilgrimages in the First Crusade and its aftermath, more crusades and pilgrims during the Ayyubid and Mamluk dynasties, pilgrimages under Ottoman rule, pilgrimages under the British and Israelis, and the unity among pilgrims and the symbolism of the journey.